Study of the hepcidin level in pregnant women with and without anemia - Aringazina, Raisa; Mussina , Aigul; Zholdassova, Nurgul; Seitmaganbetova , Nazgul (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Currently, a wide range of laboratory markers characterizing iron metabolism is available to clinicians. However, they are mainly limited by determining the hemoglobin content, iron concentration and erythrocyte morphology, which makes it impossible to differentiate iron deficiency anemia from other hypochromic anemia forms. The study aimed to evaluate the diagnostic value of hepcidin as a ferrokinetics marker under the development of anemia during pregnancy. Methods: The study included 60 pregnant women (average age 26.0±0.74 years). They were divided into two groups. The participants of the Main group had hypochromic microcytic anemia with the reference values of the red blood cells 4.15 million/µL and the hemoglobin level 105 g/L. The reference values of these marks in the Control group were 4.54 million/µL and 124.50 g/L respectively. Results: Low levels of Fe, ferritin, and hepcidin were detected in pregnant women with anemia. The serum hepcidin concentration of women with anemia was 0.55 ng/mL. The anemia-diagnosed group had a reduced ferritin level by 32% (4.5 ng/mL). This point for the Control group was 14.0 ng/mL. A positive moderate relationship was indicated for hepcidin and Fe (r=0.39; P=0.05). At the same time, a negative moderate relationship (r=-0.56; P=0.05) was found between hepcidin and ferritin. Conclusions: Data from pregnant women with anemia showed hypochromic microcytic anemia with a serum ferritin level of 4.5 ng/mL and hepcidin level of 0.55ng/mL. The present research furtherly supports the valid role of hepcidin in the diagnosis of iron deficiency anemia in pregnant women. (www.actabiomedica.it)